Perkembangan targeted therapy pada kanker payudara dengan pertimbangan luaran biaya dan kualitas hidup: narrative review - Puspitasari, Candra Eka; Annisa, Janatul; Yasykurah, Malva Marshaniswa; Hawarikatun, Baiq (Universitas Mataram, 2024)
Breast cancer is a malignant tumour that grows in the breast tissue and can spread to the lymph nodes and metastasize to other parts of the body. Targeted therapy is currently developed as a therapeutic management for breast cancer with hormone receptor positive/human epidermal growth factor receptor 2 negative (HR+/HER2-). This review aims to determine the effectiveness both in terms of clinical and cost on the use of single or combined targeted therapy when compared with conventional therapy, namely chemotherapy in breast cancer patients. The results show that the use of targeted therapy can provide greater health benefits in both single and combination use even though it can increase the cost of therapy.